In vivo Analysis of the Resistance of the Meshes to Escherichia coli Infection - Xu, Xinsen; Zhan, Ming; Li, Xinxing; Chen, Tao; Yang, Linhua (Frontiers in Surgery, 2021)
Background: The mesh infection is mostly related to the gram-negative bacteria, such as Escherichia coli (E.coli) for emergency surgery of incarcerated hernia. However, few study investigated the effects of E.coli concentration, mesh materials and antibiotic prophylaxis on mesh infection after hernioplasty. The aim of this study was to evaluate the bacterial resistance to E.coli for three different materials of mesh, and to measure the minimum E.coli concentration for mesh infection with and without antibiotic prophylaxis in a rat model. Methods: Three types of mesh (polytetrafluoroethylene, polypropylene and biologic meshes) were used in the repair of an acute ventral hernia rat model in the setting of different concentrations of E.coli loads and antibiotics. At the 8th day after surgery, mesh samples were sent for microbiologic and histologic analyses. Results: The positive rates of bacterial culture increased with E.coli concentration. The biologic mesh showed better bacterial resistance compared to polytetrafluoroethylene mesh and polypropylene mesh when the concentration of E.coli ranges from 106 CFU/ml to 108 CFU/ml (P = 0.002 and P = 0.029, respectively). Prophylactical ceftriaxone treatment could not decrease the colonization rate of E.coli at 106 CFU/ml or 108 CFU/ml in each group (P > 0.05). The scores of neovascularization in polypropylene mesh and biologic mesh were similar, which was higher than that of polytetrafluoroethylene mesh (P < 0.05). Compared with other meshes, biologic mesh showed better tolerance to 106 CFU/ml E.coli with respect to inflammation, depth of inflammation, neovascularization, cellular repopulation and foreign body giant cells. Conclusion: The biologic mesh had better E.coli resistance compared to polytetrafluoroethylene mesh and polypropylene mesh when the E.coli concentration is higher than 106 CFU/ml in rats. Antibiotic prophylaxis was useful when the contamination was not particularly severe.